FACTORS INFLUENCING BODY WEIGHTS AT DIFFERENT AGES IN THALLI SHEEP - A. Hussain; P. Akhtar; S. Ali; M. Younas; M. Yaqoob; M. E. Babar; K. Javed; A. Shakoor (Journal of Animal and Plant Sciences, 2013)
Thalli is native sheep breed of Thall area of the Punjab, Pakistan. Data on 17030 birth records of 5421 Thalli sheep maintained at Livestock Experiment Station, Rakh Ghulaman, district Bhakkar during 1975-2004 were utilized in the present study with the aim to evaluate the performance of Thalli sheep in Pakistan. The genetic parameter estimation was performed using REML procedure by fitting an Individual Animal Model. Birth weight with an average of 4.11±0.82 kg, was significantly affected by year, type of birth, sex and age of the dam but season of birth was an in significant effect on the birth weight. Weight at 60 and 90-days of age averaged 11.58±3.57 and 14.92±4.56 kg, respectively. These weights were affected by year and season of birth, birth weight. Type of birth and sex had significant effect on weight at 60 days of age where as age of the dam had non-significant effect on weight at 60 days of age. Age of the dam significantly affected 90-day weight. Sex and type of birth had non-significant effect on 90 days weight. The weaning weight was 18.95±4.12 kg and was affected by year and season of birth, sex of lamb. No significant effects of type of birth, birth weight and age of dam on weaning weight were observed. The direct heritability estimate of birth weight was 0.067±0.01. The heritability estimates for 60- and 90-day weight were 0.116±0.01 and 0.18±0.01, respectively. The heritability estimate for weaning weight was 0.03±0.11. Genetic correlation between birth weight and weaning weight was negatively low with an estimate of 0.045±0.003. The low estimates of heritability for various performance traits indicated the presence of less additive genetic variance and large environmental variances. Hence improvement in the traits through selection may be limited.
Keywords: Thalli sheep; Pre-weaning body weights; Genetic factors; Pakistan